(untitled) ("Conference on Universal Science Research 2023", 2024)
The article reports that Uzbekistan is located at the crossroads of the Great Silk Road and it is a very attractive place for tourism. Here, there are a large number of historical monuments of different civilizations, many of which are included in the UNESCO World Heritage List. Uzbekistan has a long history, originating thousands of years ago. It is noted that Uzbekistan occupies an important place in the promotion of tourism ties in the region. The publication cites the words of the Secretary General of the World Tourism Organization Taleb Rifai that “Uzbekistan has played a leading role in strengthening international cooperation in order to further development of tourism along the Silk Road.” The article stresses that as a result of attention to the development of the tourism industry from year to year the number of tourists wishing to visit Uzbekistan increase. They admire not only the natural beauty of the region, its rich history, diverse culture and unique historical monuments, and but also centuries-old traditions of the Uzbek people, its hospitality and unique cuisine.